Multicentre study on the consistency of PD-L1 immunohistochemistry as predictive test for immunotherapy in non-small cell lung cancer. Issue 7 (10th December 2019) - Butter, Rogier; 't Hart, Nils A; Hooijer, Gerrit K J; Monkhorst, Kim; Speel, Ernst-Jan; Theunissen, Paul; Thunnissen, Erik; Von der Thüsen, Jan H; Timens, Wim; van de Vijver, Marc J
Abstract : Aims: Investigate the impact of interlaboratory- and interobserver variability of immunohistochemistry on the assessment of programmed death ligand 1 (PD-L1) in non-small cell lung cancer (NSCLC). Methods: Two tissue microarrays (TMAs) were constructed from 50 (TMA-A) and 51 (TMA-B) resected NSCLC cases, and distributed among eight centres. Immunostaining for PD-L1 was performed using Agilent's 22C3 pharmDx Assay (pharmDx) and/or a 22C3 laboratory developed test (LDT). The interlaboratory variability of staining- and interobserver variability of scoring for PD-L1 were assessed in selected critical samples (samples at the cut-off of positivity) and non-critical samples. Also, PD-L1 epitope deterioration in time in stored unstained slides was analysed. Krippendorff's alpha values (0=maximal, 1=no variability) were calculated as measure for variability. Results: For interlaboratory variability of immunostaining, the percentage of PD-L1 positive cases among centres ranged 40%–51% (1% cut-off) and 23%–30% (50% cut-off). Alpha values at 1% cut-off were 0.88 (pharmDx) and 0.87 (LDT) and at 50% cut-off 0.82 (pharmDx) and 0.95 (LDT). Interobserver variability of scoring resulted in PD-L1 positive cases ranging 29%–55% (1% cut-off) and 14%–30% (50% cut-off) among pathologists. Alpha values were at 1% cut-off 0.83 (TMA-A) and 0.66 (TMA-B), and at 50% cut-off 0.77 (TMA-A) and 0.78 (TMA-B). Interlaboratory variability of staining was higher (p<0.001) in critical samples than in non-critical samples at 50% cut-off. Furthermore, PD-L1 epitope deterioration in unstained slides was observed after 12 weeks. Conclusions: The results provide insight in factors contributing to variability of immunohistochemical assessment of PD-L1, and contribute to more reliable predictive testing for PD-L1.